Листи В. Бузескула до М. Бережкова - Гордієнко, Д.С. (My University, 2013)
Статья является археографической публикацией двух писем В. Бузескула к М. Бережкову, датированных 1927 и 1928 годами. Публикуемые письма подтверждают факт личного знакомства двух ученых, дополняют, а в некоторых местах опровергают, известные факты из их биографии, а также являются важными для биографии историка А. Покровского, особенно для реконструкции его последних лет жизни. Кроме того, они отображают состояние науки и положение ученых в Советском Союзе в конце 20-х гг. ХХ в., в том числе содержат материалы, относящиеся к истории ВУАН. The article is an archeographical publication of the two V. Buzeskul’s letters to M. Berezhkov, dated 1927 and 1928. The letters being published prove the fact of personal acquaitance of the two scholars. The documents comply and in some places invalidate wide-known facts from their biographies, and are also important for the biography of the historian O. pokrovsky, especially for the reconstruction of his last years of life. Besides, the letters reflect the state of the science and scholars in the Soviet Union in the late 1920ies, among others there are materials corresponding to the history of the Ukrainian Academy of Sciences.
Keywords: В. Бузескул; М. Бережков; А. Покровский; письма; V. Buzeskul; M. Berezhkov; O. Рokrovsky; letters; Ukrainian Academy of Sciences